2014
DOI: 10.1057/sj.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

‘All walks of life’: A profile of household insurance fraudsters in the United Kingdom

Abstract: This article provides a profile of a household insurance fraudster based on an analysis of 33 189 dishonest household insurance claims identified by VFM Ltd (a claims handling company using conversation management as an investigative tool). Analysis of the dishonest claims showed marked differences in the profile of fraudsters to some of the published profiles of occupational fraudsters. There is greater gender equality and a wider range of occupations among insurance fraudsters with a peak age range in the 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Adler (1975) claimed that if given opportunities in economic positions, women would be as greedy and crime prone as men. Previous studies reported samples with more female fraudsters (e.g., AIC/PwC, 2003; Button et al, 2016) or fewer (e.g., ACFE, 2020; Steffensmeier et al, 2013). Nonetheless, Holfreter (2005) cautioned that the increased number might be due to policy changes with greater enforcement and not necessarily reflect the increase in crimes perpetrated by women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adler (1975) claimed that if given opportunities in economic positions, women would be as greedy and crime prone as men. Previous studies reported samples with more female fraudsters (e.g., AIC/PwC, 2003; Button et al, 2016) or fewer (e.g., ACFE, 2020; Steffensmeier et al, 2013). Nonetheless, Holfreter (2005) cautioned that the increased number might be due to policy changes with greater enforcement and not necessarily reflect the increase in crimes perpetrated by women.…”
Section: Resultsmentioning
confidence: 99%
“…Framed by gender theory (Holtfreter, 2015; Reisig et al, 2006) with a focus on opportunity (Andon & Free, 2020a; Free, 2015; Sykes & Matza, 1957), we examined a sample of 261 published legal cases in New Zealand between 2000 and 2020. Previous studies that focus on gender-specific forces in terms of opportunity for and rationalisation of crimes have been conducted separately (e.g., Button et al, 2016; Steffensmeier et al, 2013). The literature indicates that white-collar crime rationalisations, opportunity, and fraud nature are constrained by gender (Holtfreter, 2015; Klenowski et al, 2011), yet scholars have not adequately examined these aspects in a single study that considers different levels of legitimate hierarchical positions in the workplace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant body of research that shows that the ‘public’ see the insurance sector as an acceptable business to defraud (Button et al, 2016; Crocker & Tennyson, 2002; Tennyson, 2008). There is also research highlighting the involvement of the middle classes in a range of white ‘insurance type’ collar crimes (Button & Brooks, 2016; Wiesburd & Waring, 2001) with substantial estimates of national and international funds lost to insurance fraud (Flynn, 2015; Gee & Button, 2015).…”
Section: The Private Health Insurance Sector: Volume and Types Of Fraudmentioning
confidence: 99%
“…In particular, Clarke ( 4 ) laid the foundation of the domain of insurance fraud by examining the extent of insurance fraud and analysing similarities and differences of national responses. More recently, some researchers started to pay attention to insurance fraud and to identify a specific type of insurance fraud to fill the research gap [e.g., ( 5 , 6 )]. However, complex nature of insurance fraud and a lack of empirical data have hampered an accumulation of literature.…”
Section: Introductionmentioning
confidence: 99%